The Role of Motivation, Work Discipline and Leadership on Employee Performance in Marine Livestock Cultivation Company - Rachma Yuliana; Muhammad Amsal Nasution; Abdurohim; Fauzie Senoaji; Sartika Yuliana (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Employee performance in a company or organization is a crucial factor for business continuity and determines the company's chances of surviving in the business world. In psychology, economic motivation, good leadership and also a discipline have an indication of the good performance of employees in a company, but have major gaps in the context of the company and its own company policies. This study aims to determine the effect of Leadership, Motivation, and Discipline on Employee Performance. This study uses a quantitative approach with 72 samples taken using purposive random sampling. The research's analytical method of choice is linear regression. The findings demonstrated that while motivation and discipline have an impact on employee performance, leadership has no impact on that. Leadership, however, has an impact on performance in conjunction with motivation and discipline.